2020
DOI: 10.1007/s40843-019-1260-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion- and nucleus-acting polymeric nanoagents for chemo-photothermal combination therapy

Abstract: Developing intrinsically mitochondria-targetable nanosystems for subcellular structure-oriented precise cancer therapy is highly desirable. Here, we conjugate the cluster determinant 44 (CD44)-targetable hyaluronic acid (HA) with cholesterol-poly(ethylene glycol) 2k -NH 2 and mitochondria-acting IR825-NH 2 (a cyanine dye) to construct a self-assembled nanostructure (abbreviated as HA-IR825-Chol) for photothermal therapy. The HA-IR825-Chol exhibits improved photostability and desirable photothermal properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 78 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Chol, considered as a lipophilic anchor, was introduced into various nanosystems to enhance cellular uptake. [ 92,363 ] Liu and co‐workers conjugated the cyanine dye IR825‐NH 2 with HA and cholesterol‐PEG 2k ‐NH 2 to obtain a self‐assembled nanostructure, HA‐IR825‐Chol. [ 92 ] HA‐IR825‐Chol had excellent light stability, photothermal properties and water dispersibility.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Chol, considered as a lipophilic anchor, was introduced into various nanosystems to enhance cellular uptake. [ 92,363 ] Liu and co‐workers conjugated the cyanine dye IR825‐NH 2 with HA and cholesterol‐PEG 2k ‐NH 2 to obtain a self‐assembled nanostructure, HA‐IR825‐Chol. [ 92 ] HA‐IR825‐Chol had excellent light stability, photothermal properties and water dispersibility.…”
Section: Combination Therapymentioning
confidence: 99%
“…[ 92,363 ] Liu and co‐workers conjugated the cyanine dye IR825‐NH 2 with HA and cholesterol‐PEG 2k ‐NH 2 to obtain a self‐assembled nanostructure, HA‐IR825‐Chol. [ 92 ] HA‐IR825‐Chol had excellent light stability, photothermal properties and water dispersibility. They were also preferentially accumulated in tumor cells owing to overexpression of HA.…”
Section: Combination Therapymentioning
confidence: 99%
“…Nevertheless, rare efforts have been dedicated on developing highly photostable photothermal reagents with high PCE and large molar extinction coefficient at long irradiation wavelengths (e.g., 808 nm). Additionally, high cancer therapeutic efficacies could be achieved by the synergistic treatment of PTT with other therapeutic modalities [51][52][53][54][55]. In particular, several studies revealed that PTT showed an enhancement to the PDT efficacy for its ability to increase the blood flow rate [56][57][58].…”
Section: −•mentioning
confidence: 99%
“…Enough internalization of IR780 dye in breast carcinoma cells treated with the modified nanoparticles, and subsequent NIRlaser irradiation dramatically resulted an imbalance of intracellular ROS and phototoxicity, which further induced cancer cells death. For instance, Liu et al constructed a HA and IR825 conjugated polymeric nanosystem based on cholesterol-PEG (Chol-PEG) and encapsulated chemotherapeutics 10-hydroxycamptothecin (HCPT) into this nanocarrier (HA-IR825-Chol/HCPT) for combined chemophotothermal therapy (Liu et al, 2020). It was found that HA-IR825-Chol/HCPT exhibited significantly enhanced accumulation in mitochondria, obviously upregulated apoptosis-related proteins, and demonstrated an amplified synergistic combination therapeutic efficacy, all of which were built on the basis of IR825-mediated mitochondria targeting.…”
Section: Non-tpp Lipophilic Cations For Mitochondria Targetingmentioning
confidence: 99%